Beberapa Sifat Biologi Tanah Kebun Jeruk Siam (Citrus nobilis Tan) pada Sistem Monokultur dan Tumpangsari dengan Beberapa Tanaman Sayuran di Desa Sekaan Kecamatan Kintamani - I WAYAN BUNADA; ANAK AGUNG ISTRI KESUMADEWI; I WAYAN DANA ATMAJA (Agrotrop : Journal on Agriculture Science, 2016)
Some Biological Soil Properties of Orange Orchard (Citrus nobilis Tan)under Monoculture and Intercropping System with some Vegetable Cropsin Sekaan Village of Kintamani Districts. Orange fruit is of economically importantcommodity in Bali. The fruits mostly produced in Bangli Regency including KintamaniDistrict under intensified monoculture and intercropping with vegetable crops. Those systemspredicted contribute to variation of soil biological properties as the results of differences inmagnitude of agrochemicals that being used. A research about soil biological properties oforange orchard land was conducted in Sekaan Village of Kintamani on November 2015 -March 2016. The purpose of the study was to differenciate the soil biological propertiesamong the common cropping pattern applied in the study area, namely: monoculture oforange, and either intercropping of orange with cabbage (Brassica oleracea), tomatoes(Solanum lycopersicum), chilli (Capsicum annum L.), or cucumber (Cucumis sativus). Threereplications of rhizosperic soil samples were collected from each planting systems andproceed for selected soil analysis. The measured parameters were soil pH, organic-C, as wellas the respective total population number of soil microorganisms, fungi, Gram (+) and Gram(-) bacteria, and also soil respiration. The results showed that total population number of soilmicroorganisms and total fungi were significantly higher on intercropping compare tomonoculture systems. No significant different of those present among soils that cultivatedwith different vegetable crops. In contrary, no differences were also observed for both soilrespiration value and total number of G (+) and G (-) bacteria among soils differing incropping pattern.